2009
DOI: 10.1016/j.pbb.2009.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Hedonic sensitivity in adolescent and adult rats: Taste reactivity and voluntary sucrose consumption

Abstract: Adolescents have been hypothesized to exhibit an age-related partial anhedonia that may lead them to seek out natural and drug rewards to compensate for this attenuated hedonic sensitivity. In the present series of experiments, taste reactivity (TR) and 2 bottle choice tests were used to assess hedonic reactions to sucrose. In Exp 1, total positive taste responses to 10% sucrose solution were significantly higher in adolescent than adult rats during the infusion period. In Exp 2, adolescent animals exhibited a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
61
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 34 publications
11
61
1
1
Order By: Relevance
“…Importantly, "liking" can be measured objectively through neural responses, whether or not the individual is consciously aware of their feelings of pleasure (1). For example, human and rodent research has shown that adolescents, more so than children or adults, show heightened activation in the ventral striatum following the receipt of hedonic rewards, including money, sucrose, and immediate rather than long-term rewards (7,15,19,20). Moreover, during risk taking, adolescents show higher activation in the ventral striatum than younger or older individuals (21).…”
Section: Significancementioning
confidence: 99%
“…Importantly, "liking" can be measured objectively through neural responses, whether or not the individual is consciously aware of their feelings of pleasure (1). For example, human and rodent research has shown that adolescents, more so than children or adults, show heightened activation in the ventral striatum following the receipt of hedonic rewards, including money, sucrose, and immediate rather than long-term rewards (7,15,19,20). Moreover, during risk taking, adolescents show higher activation in the ventral striatum than younger or older individuals (21).…”
Section: Significancementioning
confidence: 99%
“…However, a growing body of evidence indicates that at least one contributing factor is an inability to control behavior in the face of reward [810, 14]. Prior studies have demonstrated an increased sensitivity to primary rewards during adolescence compared to adulthood [2, 9, 1522, 23]. Similarly, environmental cues that come to predict reward drive behaviors performed in service of obtaining reward to a greater extent in adolescents than in children or adults [1, 2, 18, 2428].…”
Section: Introductionmentioning
confidence: 99%
“…The failure to see any effects of drug pre-exposure on taste avoidance learning in adolescents could also be the result of a greater motivation to consume substances with a positive hedonic value or that they have an increased sensitivity to positive consequences Wilmouth & Spear, 2009). Specifically, if adolescents generally increase consumption of solutions with positive hedonic properties (like saccharin), such an increase might limit their ability to demonstrate a taste avoidance.…”
Section: Discussionmentioning
confidence: 99%